1998
DOI: 10.1149/1.1838525
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Nb/Fe‐Oxide Ion‐Storage Films for Counter Electrode Applications in Electrochromic Devices

Abstract: The electrochromic properties of mixed Nb/Fe-oxide films with amorphous structure which were prepared via the solgel route were determined. Films with Nb/Fe molar concentration ratios 0.2:1, 0.4:1, and 1:1 exhibit ion-storage capacities up to 18 mC/cm 2 depending on Nb/Fe molar ratio. Electrochromically films behave as optically passive electrodes with a coloration efficiency of nearly zero at X > 480 nm, while at shorter wavelengths a relatively strong anodic coloring was observed, yielding negative coloratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sputtered TiO 2 -CeO 2 films showed a capacity of 18 mC/cm 2 with high reversibility. 38 Orel et al 39 reported single-dipped SnO 2 /Mo films (100-200-nm-thick) with a high ion storage capacity of 20-30 mC/cm 2 while Nb-Fe mixed oxide films 7 were up to 18 mC/cm 2 . V 2 5 , which is ranked among the most promising ion storage films, typically possesses an ion storage capacity of up to 35 mC/cm 2 .…”
Section: Thermalmentioning
confidence: 99%
See 2 more Smart Citations
“…Sputtered TiO 2 -CeO 2 films showed a capacity of 18 mC/cm 2 with high reversibility. 38 Orel et al 39 reported single-dipped SnO 2 /Mo films (100-200-nm-thick) with a high ion storage capacity of 20-30 mC/cm 2 while Nb-Fe mixed oxide films 7 were up to 18 mC/cm 2 . V 2 5 , which is ranked among the most promising ion storage films, typically possesses an ion storage capacity of up to 35 mC/cm 2 .…”
Section: Thermalmentioning
confidence: 99%
“…Iron(III) oxide thin films are widely used for their interesting properties, for example, as catalysts in dehydrogenation reactions, magnetic devices, temperature and humidity sensors, optical filters, potential use in nonlinear optics, and so forth. , Iron oxide could also be considered as a promising electrochromic (EC) material with regard to its many valence states, which could be easily changed by either heat treatment or potential cycling in electrochemical cells. However, few studies have been done on the electrochromic properties of iron oxide films in its pure 3-6 or mixed oxide forms. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation